A set of pedagogical recommendations for improving the integrated approach to childhood obesity. (13th November 2019) - Ruiter, E L M; Molleman, G R M; Fransen, G A J; Wagenaar, M; van der Velden, K; Engels, R C M E
Abstract: Background: Studies increasingly emphasize the importance of the parents' role in interventions designed to prevent overweight in children. The aim of this study was to develop a unified set of recommendations for healthy parenting practices that can be applied by all professionals who work with children age 4-13 years and can contribute to strengthening the integrated approach to childhood overweight. Methods: A modified Delphi procedure was used to reach consensus regarding what these pedagogical recommendations should encompass. The 30 panelists were professionals and researchers who work with children in the domains of health care, overweight, parenting, education, nutrition, and/or sports. The procedure consisted of: i) extracting existing pedagogical recommendations from national guidelines and professional protocols, ii) appraising and prioritizing these recommendations in terms of relevance through two rounds of questionnaires, and iii) meeting to discuss and approve the set of recommendations. Results: Consensus was reached for one set of eleven pedagogical theme-based recommendations designed to support and instruct parents how to stimulate healthy energy balance-related behaviors in their child. Each recommendation contained information regarding: i) which behaviors are important, ii) why this is important, and iii) how parents can stimulate this behavior by applying parenting skills. The eleven themes were: modeling, positive parenting, breakfast, varied diet, sugar-sweetened beverages, snacks, physical activity, playing sports, quantity of screen time, screen time during meals, and sleep. Conclusions: We developed a set of recommendations for healthy parenting that can be used by various professionals working with children age 4-13 and can contribute to creating an integrated approach to childhood overweight. We also developed a web-based app called "Recommendations for Healthy Parenting" as a convenient tool for following these recommendations. Key messages: Our set of recommendations for healthy parenting can be used by various professionals who work with school-aged children, thereby helping strengthen the integrated approach to childhood overweight. We developed and released a Dutch web app entitled "11 Recommendations for Healthy Parenting" to provide a convenient tool for easily communicating these recommendations to parents.